51 Would a multi-ethnic Asian female population take up self-sampling HPV testing as a routine cervical screening method?. (13th November 2020) - Khoo, S; Lim, W; Nasir, N; Gravitt, P; Woo, YL
Abstract : Introduction: The uptake of the conventional cervical screening method, Pap smear remains suboptimal among Malaysian women. Vaginal self-sampling HPV testing is an alternative to improve the uptake of cervical screening. This study aims to investigate the attitudes and preferences of self-sampling HPV testing compared to Pap smear among a multi-ethnic female population. Methods: A total of 823 healthy female volunteers aged 35 to 45 were recruited from primary care clinics in urban and suburban areas in Selangor, Malaysia from June 2019 to June 2020. All participants were instructed to self-collect vaginal sample using a dry flocked swab (Copan 522C). An interview was carried out after sample collection to document sociodemographic information and self-sampling experience. Results: Of the 823 participants, 62.7% were Malays followed by 22.0% of Chinese and 12.3% of Indians. A vast majority of participants (83.4%) reported preference towards self-sampling HPV testing over Pap smear and 99.9% indicated willingness to repeat self-sampling HPV testing in 5-year time as a routine cervical screening method. The top 3 reasons for willingness to repeat this test were easy (80.9%), quick/convenient (66.3%) and not embarrassing (59.6%). Divorcees (adjusted OR: 6.08 95% CI: 1.16–31.87), full-time working women (adjusted OR: 4.00 95% CI: 1.15–10.03), housewives (adjusted OR: 4.91 95% CI: 1.57–15.41) and those who have not undergone Pap smear (adjusted OR: 1.80 95% CI: 1.08–3.01) were more likely to express preference for self-sampling HPV testing. Conclusions/Implications: Generally, Malaysian women from a relatively conservative, multi-ethnic background are willing to adopt self-sampling HPV testing as an alternative to Pap smear.